Identification of Chlamydia trachomatis with polymerase chain reaction in middle ear fluid in otitis media with effusion - Keles, E; Bulut, Y; Kaygusuz, I; Karlidag, T; Yalçin, S; Özdarendeli, A; Alpay, HC (Indian Academy Pediatrics, 2005)
In this study, 78 middle ear aspiration samples from 59 children between the ages of 2-14 who have undergone myringotomy tinder general anesthesia were included. The presence of DNA genome of Chlamydia trachomatis was analyzed with polymerase chain reaction in the aspiration material. The relationship between the nature of the effusion fluid and the presence of Chlamydia trachomatis was investigated. Of the seventy-eight middle ear effusions, 26 (33.3%) were serous, 31 were (39.7%) mucoid and 21 (26.9%) were sero-mucoid in nature. Chlamydia trachomatis DNA genome was. identified in seven (8.9%) effusion samples. Of these, three were mucoid (42.8%), three were serous (42.8%) and one was sero-mucoid (14.2%) in character. We think that during the bacteriological analyses carried out for the cases of otitis media with effusion, Chlamydia trachomatis should be taken into consideration both at the time of diagnosis and the treatment.
Keywords: Chlamydia trachomatis; otitis media with effusion (OME); polymerase chain reaction